2011
DOI: 10.1128/aem.00021-11
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Broad-Range Resequencing Array for Detection of Pathogens in Desert Dust Samples from Kuwait and Iraq

Abstract: A significant percentage of the human population is exposed to high levels of naturally occurring airborne dusts. Although the link between airborne particulate inhalation and a variety of respiratory diseases has long been established, little is known about the pathogenic role of the microbial component of the dust. In this study, we applied highly multiplexed PCR and a high-density resequencing microarray (RPM-TEI version 1.0) to screen samples of fine topsoil particles and airborne dust collected in 19 loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…Dust storms may pick up and long-range transport the toxic trace elements and biologically active compounds (bacteria, fungi, pollen, spores and viruses) from natural or anthropogenic sources on a global scale [5,[190][191][192]. All of the transported micro-organisms have potential implications for disease incidences, including meningococcal meningitis and coccidiomycosis.…”
Section: Desert Dust and Other Infectious Diseasesmentioning
confidence: 99%
“…Dust storms may pick up and long-range transport the toxic trace elements and biologically active compounds (bacteria, fungi, pollen, spores and viruses) from natural or anthropogenic sources on a global scale [5,[190][191][192]. All of the transported micro-organisms have potential implications for disease incidences, including meningococcal meningitis and coccidiomycosis.…”
Section: Desert Dust and Other Infectious Diseasesmentioning
confidence: 99%
“…Aerosol optical depth at various optical wavelengths is retrieved from measured radiances and processed through the application of various algorithms. The AOD products have been validated extensively throughout the literature mainly by comparisons with the ground-based AErosol Robotic NETwork (AERONET) observations Remer et al, 2005Remer et al, , 2008Levy et al, , 2010. The Deep Blue algorithm is an algorithm developed to overcome the problems associated with aerosol retrievals over bright-reflecting surfaces such as deserts and semiarid regions (Hsu et al, 2004(Hsu et al, , 2006.…”
Section: Synoptic Descriptionmentioning
confidence: 99%
“…Dust and dust storms interfere with human life and function in various ways. They are known to cause health problems, especially to the respiratory system, leading to various forms of allergies (Wilson and Spengler, 1996;Griffin and Kellogg, 2004;Griffin, 2007;Achudume and Oladipo, 2009;Leski et al, 2011). Dust storms cause soil loss from dry lands and preferentially remove organic matter and the nutrient-rich lightest particles, thereby reducing agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The three other studies reported the presence of C. burnetii DNA in dust (17) or primarily soil samples from a geographically large area in the United States (11,14). The latter three studies investigated the presence of C. burnetii DNA in soil samples (6) and surface swabs (1,9) in relation to human Q fever outbreaks.…”
mentioning
confidence: 99%